Histoire des Apindji d'après la tradition - Swiderski, Stanislaw (Anthropologica, 2022)
Presenting the oral-tradition history of the Apindji, this article describes the development of the political, social, and cultural life of this people, isolated from other Gabonese ethnic groups since the eighteenth century. This oral-tradition history, recently collected from among recollections of elderly Apindji, recalls the names of the first socio-political leaders of the tribe, the names of their families, as well as historical and mythical events.